1987
DOI: 10.1042/bj2420011
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-induced phosphoinositide hydrolysis in platelets. Receptor occupancy and desensitization

Abstract: The relationship between occupancy of thrombin receptors on platelets and enhanced phosphoinositide hydrolysis was analysed by examination of the dose-response relationship, the effects of thrombin inhibitors and the contribution of secondary effects. Washed human platelets were labelled with [3H]inositol, and agonist-induced accumulation of labelled inositol phosphates was measured. The dose-response curves and the time courses for alpha-thrombin- or gamma-thrombin-induced accumulation of inositol phosphates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…This would require the continued presence of proteolytically competent thrombin. It is known that hirudin, which rapidly inactivates thrombin and can strip it from its receptors, also quickly terminates PtdOH production (Holmsen et al, 1981;Huang and Detwiler, 1987), AA release and phosphoinositide breakdown (Huang and Detwiler, 1987), and causes accelerated protein differences in desensitization can also be explained by the partial dephosphorylation (this paper). This hypothesis is also supported by Huang et al (1991) who showed that an active-site inhibitor, which does not inhibit thrombin's binding to the receptor, also arrested PtdOH production.…”
Section: Discussionmentioning
confidence: 82%
“…This would require the continued presence of proteolytically competent thrombin. It is known that hirudin, which rapidly inactivates thrombin and can strip it from its receptors, also quickly terminates PtdOH production (Holmsen et al, 1981;Huang and Detwiler, 1987), AA release and phosphoinositide breakdown (Huang and Detwiler, 1987), and causes accelerated protein differences in desensitization can also be explained by the partial dephosphorylation (this paper). This hypothesis is also supported by Huang et al (1991) who showed that an active-site inhibitor, which does not inhibit thrombin's binding to the receptor, also arrested PtdOH production.…”
Section: Discussionmentioning
confidence: 82%
“…These data suggest the existence of alternate a-thrombin-stimulated pathways involved in generating early (0-1 h) and late (1)(2)(3)(4) h) increases in 1,2-diacylglycerol. An analogous situation is found in platelets, where a-thrombininduced responses can be divided into two types: those that are hirudin-sensitive (and I I I I therefore require the continual presence of ac-Ct: _E CE G tive ca-thrombin) and those that are hirudin-in-'C XC ' ' sensitive (Holmsen eta!., 1981;Huang and Detwiler, 1987). Because a-thrombin is a serine protease as well as a ligand for its own receptor, n a-thrombin-stimulated DNA differential regulation could be occurring at the um-starvedandwashedasde-level of binding and/or substrate recognition.…”
Section: Discussionmentioning
confidence: 90%
“…Several groups have demonstrated that terminating occupancy by thrombin of its platelet receptor, using hirudin, also stops inositol phospholipid hydrolysis and formation of phosphatidic acid, although aggregation and secretion are not inhibited [27][28][29]. To ensure that our observations were not due to degradation of SFLLRN, which would effectively terminate receptor occupancy, we used the aminopeptidase inhibitor amastatin to show that the decreased formation of IP 3 at 60 sec in SFLLRNstimulated platelets was not caused by degradation of SFLLRN by ectopeptidase.…”
Section: Discussionmentioning
confidence: 99%